KOMPETENSI SOSIAL GURU MENCIPTAKAN SUASANA BELAJAR MATEMATIKA KONDUSIF - Mukhbita Alya -; Indah Nola; Rike Juliansari; Ade Irma (Kampus Akademik Publiser, 2026)
This study aims to assess the social competence of teachers in the learning process. Social competence plays a key role in creating a conducive learning environment, particularly in mathematics, which is often considered difficult by students. Social competence can foster positive relationships with students, fellow teachers, and parents to support the learning process. Therefore, the social competence of mathematics teachers is a crucial factor in supporting the success of the learning process in schools.